Cistercian Monastery of S. Bento de Cástris, Évora, Portugal: Acoustic measurements under ORFEUS Project - Lanzinha, João (2018)
The Church of the Monastery of S. Bento de Cástris in Évora (13th- 19th centuries) presents an unusual space setting which seems to favour different positions for coral groups supporting liturgical and musical expression activities. These options are possibly of an empirical nature, since the scientific knowledge in the field of building physics and in particular of building acoustics are relatively recent. It is important to explore, with on-site measurements, the actual conditions of acoustic behaviour and in particular meet the reverberation times. Consequently, results obtained must be compared with the current recommendation for this type of space. This article characterises the Church in terms of its conception and its most relevant constructive aspects. The interest in measuring reverberation time, in this type of enclosed space, is also discussed. Such results of reverberation time measurements are presented and analysed for the different spaces of the Church. Finally, the findings of the study are presented as well as some hypotheses for future work in terms of acoustic analysis of Cistercian spaces and for a better understanding of the architecture and music relationship, in its different expressions.